2012
DOI: 10.1186/1471-2369-13-87
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in the type 2 diabetic patients: prevalence and associated variables in a random sample of 2642 patients of a Mediterranean area

Abstract: BackgroundKidney disease is associated with an increased total mortality and cardiovascular morbimortality in the general population and in patients with Type 2 diabetes. The aim of this study is to determine the prevalence of kidney disease and different types of renal disease in patients with type 2 diabetes (T2DM).MethodsCross-sectional study in a random sample of 2,642 T2DM patients cared for in primary care during 2007. Studied variables: demographic and clinical characteristics, pharmacological treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 35 publications
(49 reference statements)
7
30
3
2
Order By: Relevance
“…We observed that adding the SOD2 Val16Ala polymorphism to a model including the aforementioned factors increased only slightly the goodness of fit of the model (McFadden's pseudo R2 values increased from 0.361 to 0.369). Some of the factors identified in our study (male sex, duration of T2D, diastolic blood pressure, HbA1c and LDL cholesterol levels) have also been highlighted in previous studies [29,30]. However, in our sample we found that current or previous smoking was inversely associated with macroalbuminuria.…”
Section: Discussionsupporting
confidence: 83%
“…We observed that adding the SOD2 Val16Ala polymorphism to a model including the aforementioned factors increased only slightly the goodness of fit of the model (McFadden's pseudo R2 values increased from 0.361 to 0.369). Some of the factors identified in our study (male sex, duration of T2D, diastolic blood pressure, HbA1c and LDL cholesterol levels) have also been highlighted in previous studies [29,30]. However, in our sample we found that current or previous smoking was inversely associated with macroalbuminuria.…”
Section: Discussionsupporting
confidence: 83%
“…The overall prevalence of CKD observed in our study was higher than 21.8% prevalence reported from the University of Gondar Hospital study in Northwest Ethiopia [24] and closer to that of 27.5% reported in the Netherland study [25], 27.9% in the Spain PERCEDIME2 study [26] and 29.6% in the Chinese study [27]. However, our prevalence estimate of CKD using a similar definition of eGFR prediction equation was lower than that of 39% reported in Kinshasa, the democratic republic of Congo study [28], 34.1% in Catalonia (Spain) study [29], and 42.3% in the Japanese study [30]. These differences in prevalence might be because of the differences in creatinine assays and calibration, albumin assays or differences in case-mix (in terms of diabetes type).…”
Section: Discussionsupporting
confidence: 72%
“…Vinagre et al [17] found a prevalence of 20% for RI and 16.7% for albuminuria. In another study in Spain [8] the prevalence off different types of renal disease in DM2 was: 34,1% for any type of CKD, 22,9% RI and 19,5% for albuminuria. In a study performed in primary care centres in the Netherlands, van der Meer et al [18] observed that 27.6% of DM2 patients had CKD and that 13.6% of these DM2 patients had albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…CKD increases the cost of managing DM [7]. CKD commonly initiates at the prediabetes stage due to its coexistence with other CVRF, and CKD is present in one-third of DM2 patients [8]. …”
Section: Introductionmentioning
confidence: 99%